2019
DOI: 10.5194/bg-16-4671-2019
|View full text |Cite
|
Sign up to set email alerts
|

Saltwater reduces potential CO<sub>2</sub> and CH<sub>4</sub> production in peat soils from a coastal freshwater forested wetland

Abstract: Abstract. A major concern for coastal freshwater wetland function and health is the effects of saltwater intrusion on greenhouse gas production from peat soils. Coastal freshwater forested wetlands are likely to experience increased hydroperiod with rising sea level, as well as saltwater intrusion. These potential changes to wetland hydrology may also alter forested wetland structure and lead to a transition from forest to shrub/marsh wetland ecosystems. Loss of forested wetlands is already evident by dying tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Such large variations in CH 4 and N 2 O fluxes could be attributed to the within‐site differences in microtopography, soil moisture, surface vegetation cover, soil organic matter content, and soil texture, since even small differences in these site‐level conditions may cause large changes in biogeochemical responses. For example, CH 4 fluxes were significantly lower in soils of hummock than in tidal forest hollows, or small depressional areas between trees (Minick, Mitra, et al, 2019; Yu et al, 2006). Furthermore, denitrification and N 2 O flux potentials were found to be higher in hummocks with wet‐dry fluctuation than in hollows with no fluctuation (Korol & Noe, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such large variations in CH 4 and N 2 O fluxes could be attributed to the within‐site differences in microtopography, soil moisture, surface vegetation cover, soil organic matter content, and soil texture, since even small differences in these site‐level conditions may cause large changes in biogeochemical responses. For example, CH 4 fluxes were significantly lower in soils of hummock than in tidal forest hollows, or small depressional areas between trees (Minick, Mitra, et al, 2019; Yu et al, 2006). Furthermore, denitrification and N 2 O flux potentials were found to be higher in hummocks with wet‐dry fluctuation than in hollows with no fluctuation (Korol & Noe, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Limited laboratory studies also showed that CH 4 production from tidal freshwater forests tends to decline with salinity treatments (0, 2, 5 psu) (e.g., Marton et al, 2012; Minick, Kelley, et al, 2019). For example, Minick, Mitra, et al (2019) found that methane production was reduced by 98% (wood‐free incubations) and by 75%–87% (wood‐amended incubations) in saltwater treatments compared to the freshwater plus wood treatments. Reduction of CH 4 emissions at low salinity forest and marsh sites along the two rivers could be attributed to the inhibition of methanogenesis due to the increased activities of sulfate‐reducing bacteria with saltwater intrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our measured CH 4 fluxes were high despite the topsoil removal and the brackish conditions, which were expected to reduce CH 4 production, due to the removal of easily degradable carbon (Harpenslager et al, 2015;Quadra et al, 2023) and the reducing effect of salinity on CH 4 production (Van der Gon and Neue, 1995;Minick et al, 2019), respectively.…”
Section: Differences In Ch 4 Flux Of the Three Paludicropsmentioning
confidence: 97%
“…The abundance of nirS denitrifying bacteria is much greater than that of nrfA-DNRA microorganisms in the Chesapeake Bay watershed of United States, suggesting that denitrification is the primary nitrate reduction process (Franklin et al, 2017). The abundance of nrfA genes was low in tidal freshwater marshes in South Carolina of United States, suggesting weak DRNA process (Minick et al, 2019).…”
Section: Nitrogen Cycle-related Genesmentioning
confidence: 98%